Deteksi Dini Dan Edukasi Tentang Hipertensi Pada Masyarakat Rt.07 Kelurahan Jalan Gedang - Mardhatillah Febriana; Salma Septia Nabila; Kanida Dwi Pastike; Variski Nurazizah Salsabilah; Tri Lestari; Murwati Murwati (Utami Publisher, 2026)
Hypertension is a major non-communicable disease (NCD) in Indonesia and often remains undetected at the community level. This Community Service Program (KKN) was conducted in RT 07 with the aim of identifying hypertension cases, providing health education, and implementing early interventions to reduce the risk of complications. The activity consisted of four stages: preparation, door-to-door surveys, community education, and evaluation. Of the 212 residents examined, 160 were adults over 18 years old, and 26 individuals (12.26%) were found to have hypertension, predominantly within the 50–70-year age group. Major risk factors identified included high salt intake (70%), lack of physical activity (60%), and a family history of hypertension (45%). The educational intervention improved community knowledge by 35%, and 15 residents were referred to the local health center for further treatment. The results indicate that a door-to-door approach is effective in detecting hidden hypertension cases and improving public health awareness. Continuous blood pressure monitoring and community-based health education programs are essential to preventing the rise in hypertension cases and related complications.